Does inflation uncertainty hurt domestic investment? Empirical evidence from Ghana - Kofi Kamasa; Eunice Efua Kpodo; Isaac Bonuedi; Priscilla Forson (Cogent Economics & Finance)
This paper empirically investigates the effect of inflation uncertainty on domestic investment in Ghana. In addition, it investigates the differential impacts of permanent and transitory inflation uncertainty on investment in Ghana. Inflation uncertainty was measured using the conditional variance generated from the generalized autoregressive conditional heteroscedasticity (CGARCH (1, 1)) model. Employing the autoregressive distributed lag (ARDL) estimator on data covering 1970 to 2020, the results provide strong evidence that inflation uncertainty, associated with high volatility in commodity prices, hampers domestic investment in Ghana. After disaggregating total inflation uncertainty into two components, this paper finds that permanent inflation uncertainty has a stronger adverse effect on domestic investment than does transitory inflation uncertainty. Additionally, the results reveal that domestic interest rate, foreign interest rate, government expenditure, and trade openness are also important factors that significantly affect investment in Ghana. Given the economic implications of these results, this paper offers actionable policy recommendations to improve investor confidence and spur domestic investment in Ghana.